ANALISIS KEMAMPUAN MENULIS DESKRIPSI MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI POJOK - Novitaningrum, Alfidda; Purnomo, Heru; Perwitasari, Ningrum (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2024)
Education is an educator's effort to develop knowledge, morals, physical, spiritual, and personality. Indonesian is to improve reading and writing. Writing is the activity of expressing ideas through writing. Description is an essay that describes the feelings of an object. Pojok State Elementary School is an inclusive school. Some students have difficulty writing descriptions. Through this research, we can determine the extent of students' understanding of writing descriptions. Qualitative research methods use descriptive and observational data. Data collection techniques use interview, observation, and documentation techniques. The data analysis used is descriptive statistics, describing the data without making valid conclusions. The results of this research prove that writing descriptions for class IV at SDN Pojok is learning that is easy to understand. The results of the interviews and student assignment scores have good grades because students understand the concept of description, the characteristics of descriptive paragraphs, and the characteristics of descriptions and can use them through the assignment of describing their family members. Students who received the highest average result of the description writing assignment were A grades.